Case Study : Ramlah Salleh Serunding / Amalin Aisyah Mohd Nawawi - Mohd Nawawi, Amalin Aisyah (2020)
This case study assignment is to identify how the company managed their business from raw materials until its ready to market. The company that I had chosen and focused to investigate more details on is Ramlah Salleh Serunding. ‘Serunding’ is a famous as a traditional food that originating from Kelantan. Ramlah Salleh Serunding is located at Kampung Laut, Tumpat, Kelantan. Before this, I have done an interview session with the owner of the company to collect the information of the company. For instance, background of the company, organizational structure, product and services. Besides that, I also study other activities like business, marketing and strategy that used to maintain or to reach their goals. With utilization of SWOT, I learned and analysed the current condition of strengths, weaknesses, opportunities, and threats that can help development in business strategies. SWOT analysis is used because it helps to concentrate the company activities into areas where the company is strong and where the greatest opportunities lie. So, I can know and find a solution to overcome each problem that the company has faced. Besides, these alternative solutions can be practiced by the owner for business progress.